Method to develop latent fingerprints on hard and smooth surfaces impregnated with dirt - Pacheco, Edson Jorge; Antunes, Antônio Azoubel; Campello, Reginaldo Inojosa Carneiro (Revista Brasileira de Criminalística, 2023)
Forensic science has developed significantly over time in search of better results. Therefore, several techniques for lifting latent fingerprints at crime scenes were elaborated using developing agents, both physical and chemical. Most common types of surface encountered in such situations are hard and smooth ones, such as glass and metal. This note seeks to demonstrate the most appropriate technique for lifting fingerprints from hard and smooth surfaces that are impregnated with dirt, as the standard techniques (the use of cyanoacrylate and fingerprint powder for revealing prints) are impossible due to not being able to reach the excreted substances or even destroy the prints. After applying the technique, satisfactory results were achieved that allowed fingerprint comparison tests to be carried out (highlighted by results shown in photographs), representing an easy and practical solution that enables the satisfactory development of fingerprints, greatly important to the evolution of the scientific techniques applied.